Pengaruh Iklan Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Kartu Perdana Smartfren Pada Masyarakat Perumnas Muara Siban Kabupaten Lahat - Hestin Hestin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Technology brings humans into individuals who prioritize practicality in carrying out various activities. In terms of communication, cellular phones have become part of the life of modern Indonesian society as a technology that provides easy communication for its users. This background of consumer desires certainly motivates the cellular industry to compete. Advertising is very important to spur the development of products on the market in the face of competition between similar companies. In addition to paying attention to product quality, the company also pays attention to advertising which is no less important. The data collection method used in this research is literature study, which is a method used to obtain theoretical data related to the problems discussed. Then field studies, namely interviews, observations, which relate to the problem under study. to get clear data. The analytical method used in this study is qualitative, namely comparing the existing theory with the influence of advertising and product quality on purchasing decisions for Smartfren prime card products and quantitative analysis, namely data analysis using multiple linear regression statistical formulas with equations. Based on the results of research that has been carried out in the Perumnas Muara Siban Community, Lahat Regency, and the results of the analysis of the influence of advertising and product quality on purchasing decisions for Smartfren starter packs, the following conclusions can be drawn: In the t test, it was found that there was a significant effect of the advertising variable (X1) on the Purchase Decision of the Smartfren starter pack product, while the product quality variable has no effect on the purchase decision of the Smartfren starter pack. In the F test, it was found that there was a linear relationship between advertising (X1) and product quality (X2) together or simultaneously having a significant influence on the Purchase Decision of Smartfren starter pack products (Y). Of the three factors, namely advertising and product quality, the most dominant influence on the Smartfren starter pack product purchase decision is advertising. Keywords: Advertising, Product Quality and Purchase Decision